Isoniazid preventive therapy modulates Mycobacterium tuberculosis-specific T-cell responses in individuals with latent tuberculosis and type 2 diabetes - Phillip Ssekamatte; Diana Sitenda; Rose Nabatanzi; Marjorie Nakibuule; Davis Kibirige; Andrew Peter Kyazze; David Patrick Kateete; Bernard Ssentalo Bagaya; Obondo James Sande; Reinout van Crevel; Stephen Cose; Irene Andia Biraro (Scientific Reports)
Abstract Diabetes mellitus (DM) is a significant contributor to tuberculosis (TB) incidence and poor treatment outcomes. This study explored the impact of isoniazid preventive therapy (IPT) on Mycobacterium tuberculosis (Mtb)-specific T-cell memory phenotypes and function among participants with latent TB infection and DM (LTBI-DM) at baseline and after 6 months of IPT; and compared the responses to healthy controls (HC). Peripheral blood mononuclear cells were stimulated with ESAT-6 and CFP-10 peptide pools to analyse CD4+ and CD8+ T-cell responses using flow cytometry. In LTBI-DM participants, effector memory CD4+ and CD8+ T cells were decreased post-IPT, suggesting a shift towards a less-activated state or differentiation into other subsets. CXCR5 expression on both CD4+ and CD8+ T cells was upregulated, while PD-1 expression was downregulated post-IPT, indicating reduced T-cell exhaustion and improved homing capabilities. Lastly, IL-17 A and IL-13 production in CD4+ and CD8+ T cells was increased post-IPT, respectively, which play a role in enhanced Mtb infection control. The post-IPT T-cell alterations were similar to normal HC levels. These findings suggest that IPT modulates and normalises specific T-cell memory phenotypes and functional responses in LTBI-DM participants, potentially contributing to improved long-term immunity and protection against TB. This study highlights the importance of preventive therapy in high-risk populations, and larger studies with more extended follow-up are needed to assess long-lasting IPT effects.